Lechugulla (Agave lecheguilla Torr., Yucca carnerosana Trel) and Other Leaf Fibres in Northeastern Mexico: Research Needs - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez (International Journal of Economic Plants, 2017)
The present paper describes in brief the distribution, ecological conditions, morpho-anatomical characteristics and productivity of few leaf fibres specially Agave lecheguilla, Yucca carnerosana and few aspects of other species grown naturally in Northeast Mexico. The review also suggests sustainable use, conservation and propagation of these species and research needs on these species.